2022
DOI: 10.14710/jkli.21.1.73-82
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Konsentrasi COD Limbah Batik Pada Proses Seeding dan Aklimatisasi Menggunakan Material Preservasi Mikroorganisme (MPMO)

Abstract: Latar belakang: Batik merupakan warisan budaya Indonesia yang nilai ekspornya meningkat pesat. Dampak ini dapat meningkatkan pendapatan negara secara signifikan. Di sisi lain, memperluas kesempatan kerja bagi masyarakat untuk memproduksi batik. Namun , produksi batik yang besar meningkatkan volume limbah. Permasalahan ini dapat mencemari lingkungan jika limbah batik tidak terurai dengan baik. Oleh karena itu, kami mengusulkan metode bioremediasi untuk menguraikan polutan COD dalam limbah batik. Penelitian ini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The seeding process was carried out by continuously providing nutrients using tapioca, ammonium sulfate, potassium di-hydrophosphate, calcium chloride, magnesium chloride, iron (II) chloride, and nutrient broth. After the seeding process was completed, the acclimatization process is continued in the biological reactor using a batch system [18]. Then proceed with a continuous process using a mini WWTP.…”
Section: Materials and Reactor Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The seeding process was carried out by continuously providing nutrients using tapioca, ammonium sulfate, potassium di-hydrophosphate, calcium chloride, magnesium chloride, iron (II) chloride, and nutrient broth. After the seeding process was completed, the acclimatization process is continued in the biological reactor using a batch system [18]. Then proceed with a continuous process using a mini WWTP.…”
Section: Materials and Reactor Setupmentioning
confidence: 99%
“…Several research results also show that Bacillus licheniformis can reduce several types of pollutants contained in waste. For example, immobilized Bacillus licheniformis on bentonite minerals could reduce the COD concentration in batik wastewater, with the highest removal of 82% in the acclimatization process [18] and 75% in the continuous process [19]. In addition, other studies showed that immobilized or encapsulated Bacillus licheniformis had a higher ability than free cells to degrade phenol at a concentration of 3000 ppm [20].…”
Section: Introductionmentioning
confidence: 99%
“…Batik menjadi salah satu identitas budaya Indonesia yang sudah diakui The United Nations Educational, Scientific and Cultural Organization (UNESCO) (Milea, 2021). Salah satu wilayah Indonesia yang memiliki industri batik tradisional adalah Jambi Kota Seberang, Provinsi Jambi.…”
Section: Pendahuluanunclassified

Untitled

Saputra,
Utami,
Ningsih
et al. 2023
JCHEM
“…The textile industry produces dye waste which will be discharged into water bodies. Disposal of textile waste into water bodies has caused a lot of concern because of the potential health hazards associated with the entry of toxic components into the human and animal food chains (Dim, 2013), besides that it can also cause an increase in BOD and also cause water to have a high level of color (Rachmawati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%